2015
DOI: 10.1111/andr.12048
|View full text |Cite
|
Sign up to set email alerts
|

Association between etiologic factors in infertile couples and fertilization failure in conventional in vitro fertilization cycles

Abstract: SUMMARYThe aim of this study was to investigate the relationship between the etiology of the couples and risk of fertilization failure (FF) in conventional in vitro fertilization (IVF) cycles and the effect of rescue intracytoplasmic sperm injection (ICSI) technique to offspring. A total of 2542 IVF cycles were divided into four groups according to infertile etiology: Group A -primary infertility with normal semen parameters; Group B -secondary infertility with oligoasthenozoospermia; Group C -primary infertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Therefore, early cumulus cell removal was applied for patients with a higher risk of fertilization failure to avoid the excessive use of ICSI technique in clinical practice. Previous studies suggested that primary infertility and longer infertility duration were important risk factors for total fertilization failure (31,32). The incidence of total fertilization failure was also higher in patients with unexplained infertility (33,34).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, early cumulus cell removal was applied for patients with a higher risk of fertilization failure to avoid the excessive use of ICSI technique in clinical practice. Previous studies suggested that primary infertility and longer infertility duration were important risk factors for total fertilization failure (31,32). The incidence of total fertilization failure was also higher in patients with unexplained infertility (33,34).…”
Section: Discussionmentioning
confidence: 92%
“…The total fertilisation failure (TFF) refers to fertilisation failure in all oocytes. Patients with primary infertility and oligoasthenozoospermia might be at a higher risk of fertilisation failure [1]. A recent study showed that impaired sperm parameters were mainly involved in complete fertilisation failure in IVF and lower oocyte quality in intracytoplasmic sperm injection (ICSI) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, early cumulus cell removal was applied for patients with a higher risk of fertilization failure to avoid the excessive use of ICSI technique in clinical practice. Previous studies suggested that primary infertility and longer infertility duration were important risk factors for total fertilization failure [29,30]. The incidence of total fertilization failure was also higher in patients with unexplained infertility [31,32].…”
Section: Discussionmentioning
confidence: 92%